Unwrapping Heritage: Tracing the Cultural Origins and Tradition of Patupat as a Cultural Tourism Attraction in the Philippines - Remedios L. Guillermo; Divine B. Cerilo; Markjohn Z. Soriano; Micko Andrew S. Areola; Belman Millan; Bernadette Kate G. Calica (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2026)
Purpose: This study explored the historical and cultural significance of Patupat, a traditional rice cake delicacy of Ballesteros, Cagayan. It aimed to document its traditional preparation methods, examine its historical evolution, and assess its role in preserving the cultural identity and heritage of the local community. Method: The study employed a qualitative research design using semi-structured interviews with selected knowledgeable informants involved in the preparation and preservation of Patupat. Data were analyzed thematically to identify recurring patterns related to its history, preparation, cultural value, and community significance. Result: The findings revealed that Patupat is deeply embedded in the cultural traditions of Ballesteros and is commonly prepared during festivals, religious celebrations, and family gatherings. Its preparation reflects the town's agricultural resources and traditional culinary practices. The study also found that Patupat strengthens community identity, promotes intergenerational transmission of cultural knowledge, and has strong potential as a cultural tourism product. Contribution: This study contributes to the preservation of Filipino culinary heritage by providing a documented record of Patupat's history, preparation techniques, and cultural significance. The findings may serve as a reference for researchers, educators, local government units, cultural organizations, and tourism stakeholders in developing heritage conservation programs and promoting culinary tourism in Ballesteros, Cagayan.